Acceptance of montreal protocol in Malaysia through negotiation toward sustainable development: an analysis document and response of stakeholders - Nor Fairuz Abu Bakar; Muhammad Rizal Razman; Abdul Samad Hadi; Jamaluddin Md. Jahi (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2017)
Malaysia has ratified the Montreal Protocol at the international level on the basis of responsibility in support the global effort to protect the environment. It shall be the responsibility of Malaysia to implement all the principles under the Montreal Protocol at local level. There were many challenges to include various stakeholders at early stages of adoption and subsequent implementation of the Montreal Protocol in Malaysia. One of the steps used in to tackle challenges in dealing with various stakeholders is through negotiations. Based on previous studies, there are two commonly used for negotiation at the local to tackle challenges in dealing with various stakeholders are soft and hard approaches. These two forms are said to be able to influence negotiations collaboration between stakeholders in the process of negotiating to implement the international environment agreements including the Montreal Protocol at the local level. Therefore, this study aims to clarify the nature of the relationship influences by soft and hard approaches on the acceptance and subsequent implementation of the Montreal Protocol at the local level. The methods involved in this study orientated by qualitative approach. Therefore, for the purpose of data used are the documents that show the involvement of stakeholders in the process of adoption and subsequent implementation of the Montreal Protocol at the local level. This documentation is then analyzed using content analysis procedures with the help of Nvivo software. From the document analysis results indicated that the nature relationship of soft and hard approaches were interdependence in shaping consensus and cooperation of stakeholders involved.